A Robust Reinforcement Learning System Using Concept of Sliding Mode Control for Unknown Nonlinear Dynamical System - Obayashi, Masanao; Nakahara, Norihiro; Yamada, Katsumi; Kuremoto, Takashi; Kobayashi, Kunikazu; Feng, Liangbing (IntechOpen, 2011)
None